Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Housekeeping pada PT Claro Kreasi Abadi : The Influence of Work Discipline and Work Environment on the Performance of Housekeeping Employees at PT Claro Kreasi Abadi - Az Zahrah Putri Husaini; Lela Elvira; Maria Lapriska Dian Ela Revita (PT Cakrawarti Empat Proksi, 2026)
PT Claro Kreasi Abadi is a facility services provider, offering services such as housekeeping and general cleaning. This study aims to determine the influence of work discipline and the work environment—both individually and simultaneously—on employee performance at PT Claro Kreasi Abadi. This quantitative study employed multiple linear regression analysis, with data processed using SPSS version 26. A non-probability sampling technique was used, specifically a saturated sampling method involving 65 respondents. Data sources included primary data obtained through observation and questionnaires, as well as secondary data gathered via literature reviews of books and journals. The study results demonstrate that: (1) work discipline has a positive and significant partial effect on employee performance, as evidenced by a t-statistic of 5.157 (> 1.670) and a significance value (Sig.) of 0.000 (< 0.05); (2) the work environment has a positive and significant partial effect on employee performance, indicated by a t-statistic of 3.528 (> 1.670) and a significance value (Sig.) of 0.001 (< 0.05); and (3) work discipline and the work environment have a positive and significant simultaneous effect on employee performance, shown by an f-statistic of 52.140 (> 3.145) and a significance value (Sig.) of 0.000 (< 0.05).